1.8 µm passively Q-switched thulium-doped fiber laser. (December 2019) - Ahmad, H.; Sharbirin, A.S.; Ismail, M.F.
Highlights: Passively Q-switched thulium-doped fiber laser at 1.8 µm. Modulated by a single-walled carbon nanotube film saturable absorber. Output with a repetition rate of 67.9 kHz and pulse width of 1.2 µs. Observed of SNR of 40.0 dB indicates highly stable output. Abstract: This work demonstrates a simple and reliable passively Q-switched thulium-doped fiber laser capable of generating an output with a peak wavelength at 1.8 µm. Lasing is realized from the shorter wavelength region of a thulium-doped silica fiber gain medium by suppressing lasing at longer wavelengths in combination with a tunable bandpass filter. The laser is modulated by a single-walled carbon nanotube film saturable absorber. The generated Q-switched laser is capable of achieving a high repetition rate of 67.9 kHz and a narrow pulse width of 1.2 µs. As most work on the 1.6–1.8 µm waveband focuses on continuous-wave and mode-locked lasers, to the best of the author's knowledge, this is the first demonstration of a passively Q-switched thulium-doped fiber laser operating at 1.8 µm with an all-silica fiber setup. The demonstrated laser has potential for various applications including biomedical surgery and polymer-based welding applications.